Scalable geometric routing scheme based on location-independent names - Yanbin SUN; Yu ZHANG; Hongli ZHANG; Binxing FANG (Dianxin kexue)
Name-based routing has become one of the hot topics in future network.However,due to the sustained growth of the size of nodes and information,the scalability issue is becoming one of the bottlenecks of name-based routing.As a new type of scalable routing,geometric routing provides both scalable routing tables and low routing paths,but it is difficult to support name-based routing.A universal scalable geometric routing scheme based on location-independent names（GRIN）was proposed.GRIN implemented a hybrid geometric routing（HGR）combining greedy routing with source routing,introduced a distributed name resolution using 2-level sloppy groups.Then the state and the path stretch upper bound of GRIN were analyzed.The simulation results show that GRIN guarantees scalability,low stretch and reliability.It outperformanced other similar routing schemes.